Protocol for the Collection of Nail Matrix Biopsies in Corpses (2016)
Introduction: The gold standard for the diagnosis of subungual melanocytic lesions is the histopathological study. Parameters such as number, morphological characteristics and location of melanocytes in the nail apparatus are essential to differentiate benign lesions from nail melanoma, malignant neoplasm of aggressive behavior and poor prognosis. In our country, there have been no studies aimed at quantifying melanocytes in the normal nail matrix or pigmented lesions of the nails. For this reason, a research project was carried out to determine the mean number of melanocytes in the normal nail matrix, including the creation of a protocol for the collection of nail matrix biopsies in corpses. Materials and methods: Nail matrix biopsies of the first finger and toe, of the right hand and foot,were performed on 41 Colombian mestizo cadavers without macroscopic evidence of nail lesions following the sampling protocol described in this article. Results and discussion: The protocol for collecting nail matrix biopsies in corpses consists of five steps: nail inspection, dissection and avulsion of the nail plate, collection of two longitudinal nail matrix biopsies,repositioning and fixing of the plate, and fixing of the nail folds. Conclusions: The protocol  created allows to obtain nail matrix biopsies without important aesthetic alterations, while providing good quality samples.